Unveiling the Complex Characters in The Glass Menagerie: A Psychological Analysis of Intriguing Personalities - Zulkarnain, Zulkarnain; Kurniawan, Redite; Widiati, Bidarita; Fachrurrozi, Fachrurrozi (Universitas Pendidikan Mandalika, 2024)
Literature serves as a reflective medium that captures and articulates the intricacies of social reality, providing a profound portrayal of real-life phenomena. It functions as a vital record, encapsulating the observations and perceptions of individuals in their lived experiences. In essence, literature is an eloquent description of life itself. This study specifically delves into the exploration of personalities within the context of the play